Risk communication and community engagement as an emerging pillar of health emergency management in Iran: Achievements and the way forward - Senga, Mikiko; Kouhestani, Marzieh; Hosseini Boroujeni, Sayed Mohsen; Ghaderi, Ebrahim; Parchami, Peyman; Hussain, Syed Jaffar (Frontiers in Public Health, 2023)
Risk communication and community engagement (RCCE) is an essential component of emergency preparedness and response. In Iran, RCCE is a relatively new area of public health. During the COVID-19 pandemic in Iran, the national task force relied on conventional methods, which is to utilize existing primary health care (PHC) structure to implement RCCE activities around the country. The PHC network and the community health volunteers embedded in it enabled the country to bridge the health system and communities from the very beginning of the COVID-19 pandemic. The RCCE strategy to respond to COVID-19 was adapted over time with the development of a national program, commonly known as the “Shahid Qassem Soleimani” project. This project consisted of six steps including case detection, laboratory testing through the establishment of sampling centers, scale up of clinical care to vulnerable groups, contact tracing, home care for vulnerable population, and COVID-19 vaccination roll out. Nearly three years into the pandemic, the importance of designing RCCE for all types of emergencies, allocating a dedicated team to RCCE, coordinating with different stakeholders, improving the capacity of RCCE focal points, practicing more efficient social listening, and using social insight for better planning were identified as some lessons learned. Further, Iran’s RCCE experience during the COVID-19 pandemic underscores the importance of continuing to invest in the health system, particularly PHC.